A Review of Electric Corn Thresher Machine for Post-Harvest Efficiency of Small-Scale Corn Farmers - idris, Ahmad Zaki; Massaguni, Massriyady (UPPM Poltek ATI Makassar, 2024)
Using electric corn threshers is a significant innovation in improving post-harvest efficiency for small-scale corn farmers. This tool increases efficiency and productivity, allowing farmers to process their crops faster and less laboriously. This article explores electric corn threshers' technical and economic aspects, including their design, operational performance, and impact on harvest efficiency and farmer productivity. The review highlights this technology's key benefits and challenges faced in its implementation and provides recommendations for further development to support more sustainable corn farming in the future. The use of electric small-scale corn threshers has helped corn farmers significantly improve their post-harvest efficiency. This article reviews the technical and economic aspects of small-scale electric corn threshers, including their design, operational performance, and their impact on harvest efficiency and farmers’ economic returns. The review also explores the key benefits gained from the use of these machines, the challenges faced in their implementation, and potential technological developments that can further support the corn farming sector in the future. With a comprehensive approach, this article provides a holistic view of the contribution of electric corn threshers to improving the operational efficiency and economic sustainability of farmers.